Separator for electrochemical device and electrochemical device including said separator
Patent Information
- Application Number
- JP2024544506
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-26
- Filing Date
- 2023-01-26
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2043-01-26
AI Technical Summary
【0029】 本発明の一具現例による電気化学素子用分離膜は、接着力が向上するとともに、メルトダウン温度が高くて高温における分離膜の収縮率が低く、耐熱性及び寸法安定性に優れる。
Smart Images

Figure 2025504923000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a separator for an electrochemical device, and an electrochemical device including the separator.
[0002] This application claims priority to Korean Patent Application No. 10-2022-0011687, filed on January 26, 2022, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]
[0003] Recently, interest in energy storage technology has been increasing. As the fields of application expand to include energy for mobile phones, camcorders, and laptops, as well as electric vehicles, efforts in research and development of electrochemical elements are gradually becoming more concrete. Among these, interest is being shown in the development of secondary batteries, which are energy storage devices that can be charged and discharged based on electrochemical principles. In addition, in the development of such batteries, research and development related to new electrode and battery designs has been conducted recently in order to improve the capacity density and specific energy.
[0004] Lithium-ion secondary batteries, in particular, are batteries that can be used repeatedly because lithium ions store and generate electricity by going back and forth between positive and negative electrodes. Lithium-ion secondary batteries are characterized by high voltage and energy density, long cycle life, excellent storage properties, and high output, and are therefore being applied in a wide range of fields, including portable IT devices, batteries for electric vehicles, and energy storage systems (ESS). Among these, the spread of electric vehicles is the main key to the growth of secondary batteries and is the main growth driver of the secondary battery market.
[0005] The four main components of such a secondary battery are a positive electrode, a negative electrode, an electrolyte, and a separator. Among these, the separator separates the two electrodes in the secondary battery, the positive electrode and the negative electrode, to prevent electrical shorting caused by physical contact, and provides a path through which ions can move between the two electrodes via the electrolyte held in the micropores, thereby providing ion conductivity.
[0006] Such separation membranes are made of microporous polymer film materials having the above-mentioned functions, and polyolefin-based separation membranes are particularly widely used. Representative polyolefin-based separation membranes include polyethylene (PE)-based and polypropylene (PP)-based polymer materials.
[0007] The manufacturing methods for forming such a microporous structure are broadly divided into a dry process based on a stretching process and a wet process based on an extraction process, and a dry separation membrane or a wet separation membrane is used depending on the desired characteristics.
[0008] Meanwhile, when a wet separator using polyolefin is applied to a secondary battery, there is a problem that the heat resistance is insufficient, as a meltdown phenomenon occurs when the temperature of the battery rises above the melting point of the polyolefin, resulting in fire and explosion. To solve this problem, a technology has been developed in which the surface of the separator is coated with inorganic particles and a binder polymer. As part of this, a ceramic-coated safety reinforced separator (SRS) has been developed and is applied to lithium-ion secondary batteries for electric vehicles, becoming the standard for heat-resistant separator technology. To manufacture such separators, wet separators that are easy to make thin are mainly used.
[0009] As a method for producing such a wet separation membrane, a method of coating a dry film with a polymer binder using an immersion phase separation method, which is a nonsolvent induced phase separation method (NIPS), has been researched and developed.
[0010] This method has the advantage of being advantageous in terms of resistance due to the thinning of the separator, but it is still disadvantageous in terms of dimensional stability due to heat, and there is a problem that microvoids and macrovoids are generated due to a decrease in packing density depending on the composition and process. Summary of the Invention [Problem to be solved by the invention]
[0011] An object of the present invention is to provide a separator for electrochemical devices which has excellent adhesive strength and ensures safety at high temperatures.
[0012] Another object of the present invention is to provide a method for producing a separator for electrochemical elements using an immersion phase separation method, which has excellent adhesive strength and ensures safety at high temperatures.
[0013] It will be readily apparent to those skilled in the art that other objects and advantages of the present invention can be realized by the means or methods recited in the claims and combinations thereof. [Means for solving the problem]
[0014] The present inventors have found that the above-mentioned problems can be solved by the following separator for an electrochemical device, an electrochemical device having the same, and a method for manufacturing the same.
[0015] The first embodiment is A separator for an electrochemical element, comprising: The separation membrane comprises a polymeric porous support and an inorganic composite porous layer formed on at least one surface of the porous support, The inorganic composite porous layer contains a binder polymer and an inorganic filler, the binder polymer comprises a first binder polymer and a second binder polymer, The ratio of the weight of the first binder polymer to the weight of the second binder polymer is 6:4 to 9:1; The first binder polymer is a non-crystalline polymer having a glass transition temperature (Tg) of 180° C. or more, the second binder polymer is a polyvinylidene fluoride copolymer including a first repeating unit derived from vinylidene fluoride (VDF) and a second repeating unit derived from hexafluoropropylene (HFP); The present invention relates to a separator for an electrochemical device, wherein the content of the second repeating unit is 4 to 40% by weight based on the total weight of the polyvinylidene fluoride copolymer.
[0016] The second embodiment is the same as the first embodiment, The separator for an electrochemical device, wherein the ratio of the weight of the first binder polymer to the weight of the second binder polymer is 6:4 to 7:3.
[0017] The third embodiment is the first or second embodiment, The present invention relates to a separator for an electrochemical device, wherein the content of the second repeating unit is 4 to 15% by weight based on the total weight of the polyvinylidene fluoride copolymer.
[0018] The fourth embodiment is any one of the first to third embodiments, The present invention relates to a separator for electrochemical devices, wherein the inorganic composite porous layer has a porosity of 70% or more.
[0019] The fifth embodiment is any one of the first to fourth embodiments, The present invention relates to a separator for an electrochemical element, wherein the first binder polymer comprises polyimide (PI), polyamideimide (PAI), polyetherimide (PEI), polyphenylsulfone (PPSU), polyethersulfone (PES), polysulfone (PSU), or two or more of these.
[0020] The sixth embodiment is any one of the first to fifth embodiments, The present invention relates to a separator for an electrochemical device, wherein the inorganic filler is primary particles having an average particle size of 20 nm to 700 nm.
[0021] The seventh embodiment is any one of the first to sixth embodiments, The present invention relates to a separator for an electrochemical element, wherein the inorganic filler comprises alumina (Al2O3), fumed alumina, aluminum hydroxide (Al(OH)3), magnesium hydroxide (Mg(OH)2), boehmite (AlOOH), or two or more of these.
[0022] The eighth embodiment is any one of the first to seventh embodiments, The present invention relates to a separator for an electrochemical device, wherein the inorganic composite porous layer further contains 3 parts by weight or less of a dispersant per 100 parts by weight of the inorganic composite porous layer.
[0023] The ninth embodiment is the eighth embodiment, The present invention relates to a separator for an electrochemical element, wherein the dispersant is polyvinylpyrrolidone (PVP).
[0024] The tenth embodiment relates to an electrochemical device including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, wherein the separator is a separator for an electrochemical device according to any one of the first to ninth embodiments.
[0025] The eleventh embodiment is the tenth embodiment, The electrochemical device is a lithium secondary battery.
[0026] The twelfth embodiment is a method for manufacturing a separator for an electrochemical device according to any one of the first to ninth embodiments, (S1) preparing a polymeric porous support; (S2) applying a slurry containing a binder polymer, an inorganic filler, and a solvent to at least one surface of the polymeric porous support; (S3) immersing the polymeric porous support coated with the slurry in a composition containing a non-solvent and drying the composition to form an inorganic composite porous layer; the binder polymer comprises a first binder polymer and a second binder polymer, The ratio of the weight of the first binder polymer to the weight of the second binder polymer is 6:4 to 9:1; The first binder polymer is a non-crystalline polymer having a glass transition temperature (Tg) of 180° C. or more, the second binder polymer is a polyvinylidene fluoride copolymer including a first repeating unit derived from vinylidene fluoride (VDF) and a second repeating unit derived from hexafluoropropylene (HFP); The present invention relates to a method for producing a separator for an electrochemical device, wherein the content of the second repeating unit is 4 to 40% by weight based on the total weight of the polyvinylidene fluoride copolymer.
[0027] The thirteenth embodiment is the twelfth embodiment, The present invention relates to a method for producing a separator for an electrochemical element, wherein the solvent is an organic solvent.
[0028] The 14th embodiment is the 12th or 13th embodiment, The present invention relates to a method for producing a separator for an electrochemical element, wherein the non-solvent comprises water, methanol, ethanol, propyl alcohol, butyl alcohol, butanediol, ethylene glycol, propylene glycol, tripropylene glycol, acetone, tetrahydrofuran, methylene chloride, chloroform, dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone, cyclohexane, isopropyl alcohol, or two or more of these. Effect of the Invention
[0029] The separator for an electrochemical device according to an embodiment of the present invention has improved adhesive strength, a high meltdown temperature, and a low separator shrinkage rate at high temperatures, and thus has excellent heat resistance and dimensional stability.
[0030] Therefore, the high temperature safety of a battery manufactured using a separator according to an embodiment of the present invention can be improved.
[0031] The drawings attached to this specification are intended to illustrate preferred embodiments of the present invention and serve to further understand the technical ideas of the present invention as well as the contents of the invention, and therefore the present invention should not be interpreted as being limited to only the matters described in the drawings. Meanwhile, the shape, size, scale, or ratio of elements in the drawings attached to this specification may be exaggerated in order to emphasize a clearer description. [Brief description of the drawings]
[0032] [Figure 1a] 1 is a SEM image of a cross section of the separation membrane according to Example 1 (magnification: 1000 times). [Figure 1b] 1 is a SEM image of a cross section of the separation membrane according to Example 1 (magnification: 3000 times). [Figure 2a] 1 is a SEM image of a cross section of the separation membrane according to Example 2 (magnification: 1000 times). [Figure 2b] 1 is a SEM image of a cross section of the separation membrane according to Example 2 (magnification: 3000 times). [Figure 3a] 1 is a SEM image of a cross section of the separation membrane according to Example 3 (magnification: 1000 times). [Figure 3b] 1 is a SEM image of a cross section of the separation membrane according to Example 3 (magnification: 3000 times). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0033] The present invention will be described in detail below. The terms and words used in the present specification and claims should not be interpreted as being limited to their ordinary and dictionary meanings, but should be interpreted as having meanings and concepts that correspond to the technical ideas of the present invention, based on the principle that the inventor himself can appropriately define the concepts of terms in order to best describe the invention.
[0034] Throughout this specification, when a part "comprises" another component, it means that the part may further include the other component, not excluding the other component, unless otherwise specified.
[0035] In addition, the term "about" is used throughout this specification to mean a numerical value or close to a numerical value when given the inherent manufacturing and material tolerances, and is used to prevent unconscionable infringers from unfairly taking advantage of the contents of the disclosure in which precise or absolute numerical values are recited to aid in the understanding of this application.
[0036] Throughout this specification, the phrase "A and / or B" means "A, B, or both."
[0037] According to an embodiment of the present invention, a separator for an electrochemical device is The porous support includes a polymeric porous support and an inorganic composite porous layer formed on at least one surface of the porous support, The inorganic composite porous layer contains a binder polymer and an inorganic filler, the binder polymer comprises a first binder polymer and a second binder polymer, The ratio of the weight of the first binder polymer to the weight of the second binder polymer is 6:4 to 8:2; The first binder polymer is a non-crystalline polymer having a glass transition temperature (Tg) of 180° C. or more, the second binder polymer is a polyvinylidene fluoride copolymer including a first repeating unit derived from vinylidene fluoride (VDF) and a second repeating unit derived from hexafluoropropylene (HFP); The content of the second repeating unit is 4 to 40% by weight based on the total weight of the polyvinylidene fluoride copolymer.
[0038] According to an embodiment of the present invention, the polymeric porous support is not limited as long as it has a structure having pores, and may be a porous polymer substrate, specifically, a porous polymer film substrate or a porous polymer nonwoven fabric substrate.
[0039] The porous polymer film substrate may be a porous polymer film containing a polyolefin such as polyethylene or polypropylene, and such a polyolefin porous polymer film substrate exhibits a shutdown function at a temperature of, for example, 80 to 130°C.
[0040] In this case, the porous polymer film may be formed from a polyolefin polymer such as polyethylene (high density polyethylene, linear low density polyethylene, low density polyethylene, ultra-molecular weight polyethylene, etc.), polypropylene, polybutylene, polypentene, etc., a mixture of two or more of these polymers, or a derivative thereof.
[0041] Representative examples of commercially available polyolefin porous polymer films that can be used as such polymeric porous supports include, but are not limited to, wet polyethylene systems (Asahi Kasei E-Materials, Toray, SK I.E. Technology, Shanghai Energy, Sinoma, Entek), dry polypropylene systems (Shenzhen Senior, Cangzhou Mingzhu), and dry polypropylene / polyethylene multilayer structures (Polypore, Ube).
[0042] In addition, the porous polymer film substrate may be manufactured by forming various polymers such as polyester in addition to polyolefin into a film shape. In addition, the porous polymer film substrate may be formed in a structure in which two or more film layers are laminated, and each film layer may be formed from the above-mentioned polymers such as polyolefin and polyester alone or a mixture of two or more of them.
[0043] In addition, the porous polymer film substrate and the porous nonwoven fabric substrate may be formed from a polymer such as polyester (e.g., polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc.), polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, etc., either alone or in combination, in addition to the above-mentioned polyolefin-based polymers.
[0044] The thickness of the polymeric porous support is not particularly limited, but may be 1 μm or more, 3 μm or more, 15 μm or less, or 10 μm or less. When the thickness of the polymeric porous support satisfies this range, the problem of acting as a resistance layer can be improved while maintaining mechanical properties.
[0045] The pore size and porosity of the polymeric porous support are not particularly limited, but the porosity may be in the range of 10 to 95%, and the pore size (diameter) may be in the range of 0.1 to 50 μm. When the pore size and porosity are in such ranges, the problem of acting as a resistance layer can be prevented and mechanical properties can be maintained. In addition, the polymeric porous support may be in the form of a fiber or membrane.
[0046] The inorganic composite porous layer is located on one surface of the polymeric porous support and includes a binder polymer and an inorganic filler.
[0047] The inorganic composite porous layer is one of the constituent layers of the separator, and serves as an isolating layer to prevent short-circuiting between the positive electrode and the negative electrode, and at the same time, prevents the polymer porous support from directly contacting lithium metal.
[0048] In the inorganic composite porous layer, inorganic fillers are filled and bound to each other by the binder polymer in a state of contact with each other, so that an interstitial volume is formed between the inorganic fillers, and the interstitial volume between the inorganic fillers becomes an empty space to form a pore. That is, the binder polymer adheres the inorganic fillers so as to maintain the bound state between the inorganic fillers, for example, the binder polymer connects and fixes the inorganic fillers to each other. Also, the pores of the inorganic composite porous layer are pores formed when the interstitial volume between the inorganic fillers becomes an empty space, and are spaces limited by inorganic fillers that are substantially in contact with each other in a packed structure (closed packed or densely packed) by the inorganic fillers.
[0049] The inorganic filler serves to form micropores by allowing spaces to be formed between the inorganic fillers, and also serves as a kind of spacer that allows the physical shape to be maintained. Generally, the inorganic filler has physical properties that do not change even at high temperatures of 200°C or higher, so the organic / inorganic composite porous film formed has excellent heat resistance.
[0050] Therefore, in a lithium secondary battery including the separator, even if the polymer porous support ruptures inside the battery under harsh conditions due to internal or external factors such as high temperature, overcharging, or external impact, the inorganic composite porous layer can prevent both electrodes from being completely short-circuited. Even if a short circuit does occur, the short-circuited area can be prevented from expanding, thereby improving the safety of the battery.
[0051] In one embodiment of the present invention, the porosity of the inorganic composite porous layer may be 70% or more. Specifically, the porosity of the inorganic composite porous layer may be determined depending on the composition of the inorganic composite porous layer, and may be in the range of 70% to 85% or 75% to 83%. When the porosity of the inorganic composite porous layer satisfies such a range, an effect of reducing resistance is achieved.
[0052] The thickness of the inorganic composite porous layer may be in the range of 1 μm or more, 3 μm or more, 50 μm or less, 30 μm or less, or 20 μm or less.
[0053] The inorganic filler is not particularly limited as long as it is electrochemically stable. In other words, the inorganic filler that can be used in the present invention is a filler that can be used in the range of the operating voltage of the applied battery (for example, Li / Li + There is no particular limitation as long as the inorganic filler does not undergo oxidation and / or reduction reactions at a voltage of 0 to 5 V relative to the reference voltage. Examples of such inorganic fillers include alumina (Al2O3), fumed alumina, aluminum hydroxide (Al(OH)3), magnesium hydroxide (Mg(OH)2), boehmite (AlOOH), or a mixture of two or more of these. Specifically, alumina (Al2O3) may be used.
[0054] The inorganic filler preferably has an average particle size (D50) in the range of 20 nm to 700 nm in order to form an inorganic composite porous layer with a uniform thickness and a suitable porosity. Specifically, it may be in the range of 100 nm to 500 nm. When the inorganic filler has an average particle size (D50) in this range, the dispersion of the slurry for the inorganic composite porous layer is maintained, making it easy to control the physical properties of the separator, and preventing problems such as an excessive increase in the thickness of the separator resulting in a decrease in mechanical properties or an excessively large pore size causing an internal short circuit during charging and discharging of the battery. In addition, the packing density increases, contributing to the thermal shrinkage rate, and the particle size in the above range can exhibit excellent high heat resistance.
[0055] In the present invention, the average particle size (D50) of the inorganic filler is defined as the particle size based on 50% of the particle size distribution. In the present invention, the average particle size (D50) of the inorganic filler can be measured by, for example, observation with an electron microscope using a scanning electron microscope (SEM) or a field emission scanning electron microscope (FE-SEM), or by using a laser diffraction method. When measuring by the laser diffraction method, more specifically, the inorganic filler is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT3000), and is irradiated with ultrasonic waves of about 28 kHz at an output of 60 W, and the average particle size (D50) based on 50% of the particle size distribution in the measuring device can be calculated.
[0056] The inorganic filler may be a primary particle that is a single particle, or a secondary particle formed from an aggregate of primary particles.
[0057] The content of the inorganic filler is not particularly limited, and may be 50% by weight or more, 60% by weight or more, 95% by weight or less, 97% by weight or less, or 99% by weight or less, based on the total weight of the inorganic composite porous layer. That is, the weight ratio of the inorganic filler to the binder polymer may be 50:50 or more, 60:40 or more, 70:30 or more, 95:5 or less, 97:3 or less, or 99:1 or less, and may be 50:50 to 99:1, more specifically 60:40 to 97:3, and more specifically 70:30 to 95:5. When the content of the inorganic filler satisfies the above range, it is possible to prevent a problem of a decrease in pore size and porosity of the inorganic composite porous layer formed due to an excessive content of the binder polymer, and also to solve a problem of a decrease in adhesive strength between inorganic materials due to a decrease in the content of the binder polymer, thereby deteriorating the peel resistance of the inorganic composite porous layer.
[0058] The binder polymer includes a first binder polymer and a second binder polymer. Preferably, the binder polymer may be substantially composed of the first binder polymer and the second binder polymer. Here, the term "substantially" means that although a small or trace amount of impurities or other components is inevitably contained in the manufacturing process, the amount of the impurities or other components does not significantly affect the object of the present invention.
[0059] The first binder polymer is an amorphous polymer having a glass transition temperature (Tg) of 180° C. or more. Specifically, the first binder polymer may be an amorphous polymer having a glass transition temperature (Tg) of 180° C. to 350° C. For example, the amorphous binder polymer may be, but is not limited to, polyimide (PI), polyamideimide (PAI), polyetherimide (PEI), polyphenylsulfone (PPSU), polyethersulfone (PES), polysulfone (PSU), or a mixture of two or more of these. Specifically, the glass transition temperature of the amorphous binder polymer is about 250 to 340° C. for polyimide, about 280 to 290° C. for polyamideimide, about 217° C. for polyetherimide, about 222° C. for polyphenylsulfone, about 230° C. for polyethersulfone, and about 185° C. for polysulfone.
[0060] The second binder polymer is a polyvinylidene fluoride copolymer including a first repeating unit derived from vinylidene fluoride (VDF) and a second repeating unit derived from hexafluoropropylene (HFP). Preferably, the second binder polymer is a polyvinylidene fluoride copolymer substantially composed of the first repeating unit and the second repeating unit.
[0061] The content of the second repeating unit is 4 to 40 wt % based on the total weight of the polyvinylidene fluoride copolymer. Specifically, it may be 4 to 15 wt %. If the content of the second repeating unit is less than the above range, the solubility in the solvent is low, making it difficult to control the process, and the phase separation speed is fast, resulting in a decrease in the binding strength in the coating layer. If the content of the second repeating unit is more than the above range, the solubility in the solvent is high, making it difficult to achieve phase separation characteristics. Therefore, it is advantageous for the content of the second repeating unit to satisfy the above range in terms of contributing to the adhesive strength with the electrode.
[0062] In the present invention, the ratio by weight of the first binder polymer to the second binder polymer is 6:4 to 9:1, specifically, 6:4 to 7:3.
[0063] When the ratio of the weight of the first binder polymer to the weight of the second binder polymer is within the above range, it is more advantageous in terms of adhesive strength and voltage resistance. For example, when the weight of the first binder polymer is out of the above range, the heat resistance and voltage resistance may be deteriorated.
[0064] The inorganic composite porous layer may further contain other additives such as a dispersant and a flame retardant, as necessary, in addition to the binder resin and the inorganic filler as components of the inorganic composite porous layer.
[0065] According to an embodiment of the present invention, the inorganic composite porous layer may further include 3 parts by weight or less of a dispersant based on 100 parts by weight of the inorganic composite porous layer. In this case, the dispersant may be polyvinylpyrrolidone (PVP). The inclusion of the dispersant increases the hydrophilicity of the first binder polymer, which contributes to the dispersibility of the inorganic filler. Furthermore, the binding strength between the inorganic composite porous layer and the polymeric porous support is increased.
[0066] According to one embodiment of the present invention, 1 is a method for producing a separator for an electrochemical device according to an embodiment of the present invention, (S1) preparing a polymeric porous support; (S2) applying a slurry containing a binder polymer, an inorganic filler, and a solvent to at least one surface of the polymeric porous support; (S3) immersing the polymeric porous support coated with the slurry in a composition containing a non-solvent and drying the composition to form an inorganic composite porous layer; the binder polymer comprises a first binder polymer and a second binder polymer, The ratio of the weight of the first binder polymer to the weight of the second binder polymer is 6:4 to 9:1; The first binder polymer is a non-crystalline polymer having a glass transition temperature (Tg) of 180° C. or more, the second binder polymer is a polyvinylidene fluoride copolymer including a first repeating unit derived from vinylidene fluoride (VDF) and a second repeating unit derived from hexafluoropropylene (HFP); The content of the second repeating unit is 4 to 40 wt % based on the total weight of the polyvinylidene fluoride copolymer, and the method for producing the separator for an electrochemical device is provided.
[0067] When the inorganic filler is applied to the inorganic composite porous layer, the slurry may be prepared by dissolving the binder polymer in a solvent (which may be a dispersion medium for the inorganic filler), adding the inorganic filler, and dispersing the resultant. Specifically, in the present invention, the binder polymer including the first binder polymer and the second binder polymer is dissolved in an organic solvent, and then the inorganic filler is added and dispersed. In this case, the inorganic filler may be added in a state of being crushed to an appropriate size, or the inorganic filler may be added to a binder polymer solution, and then crushed and dispersed by a ball mill method or the like.
[0068] The solvent may have a solubility index similar to that of the binder polymer and a low boiling point. This is to facilitate uniform mixing and subsequent solvent removal. Such a solvent may be an organic solvent. Specifically, the solvent may be one compound or a mixture of two or more compounds selected from acetone, tetrahydrofuran, methylene chloride, chloroform, dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone, cyclohexane, methanol, ethanol, and isopropyl alcohol.
[0069] In this case, the solvent may function as a solvent for dissolving the binder polymer or as a dispersion medium for dispersing the binder polymer, depending on the type of the binder polymer to be mixed.
[0070] According to an embodiment of the present invention, the method of coating the slurry on the polymeric porous support includes a pre-metering method and a post-metering method. The pre-metering method is a method in which a coating amount is determined in advance and introduced, such as slot die coating and gravure coating. The post-metering method is a method in which a sufficient amount of the slurry, which is a coating liquid, is applied to the polymeric porous support, and then a specified amount is scraped off, such as bar coating. There is also a direct-metering coating method that combines the pre-metering method and the post-metering method.
[0071] The slurry can be applied by a method such as the above-mentioned method, and the polymeric porous support to which the slurry has been applied can be immersed in a composition containing a non-solvent to cause phase separation and form an inorganic composite porous layer.
[0072] According to one embodiment of the present invention, the non-solvent may be an aqueous solvent or an aqueous solvent mixed with an oil-based solvent. For example, the non-solvent may include water, methanol, ethanol, propyl alcohol, butyl alcohol, butanediol, ethylene glycol, propylene glycol, tripropylene glycol, acetone, tetrahydrofuran, methylene chloride, chloroform, dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone, cyclohexane, isopropyl alcohol, or two or more of these. Specifically, the non-solvent may be water mixed with N-methyl-2-pyrrolidone or water mixed with dimethylacetamide.
[0073] The electrochemical device according to the embodiment of the present invention includes a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, and the separator is the separator according to the embodiment of the present invention described above.
[0074] The electrode to be used with the separator of the present invention is not particularly limited, and may be prepared by bonding an electrode active material to an electrode current collector by a conventional method well known in the art.
[0075] Non-limiting examples of the positive electrode active material among the electrode active materials include conventional positive electrode active materials used in the positive electrodes of conventional lithium secondary batteries, and in particular, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium iron oxide, or a lithium composite oxide obtained by combining these materials.
[0076] Non-limiting examples of the negative electrode active material include conventional negative electrode active materials used in the negative electrodes of conventional lithium secondary batteries, and in particular, lithium metal or lithium alloys, carbon, petroleum coke, activated carbon, graphite, other carbons, and other lithium adsorbent materials are preferred.
[0077] Non-limiting examples of positive current collectors include foils made of aluminum, nickel, or combinations thereof, and non-limiting examples of negative current collectors include foils made of copper, gold, nickel, or copper alloys, or combinations thereof.
[0078] The electrolyte used in the electrochemical element according to one embodiment of the present invention is + B - and the like, + Li + , Na + , K + or a combination thereof, - PF6 - , BF4 - , Cl - , Br - , I - , ClO4 - , AsF6 - , CH3CO2 - , CF3SO3 - , N(CF3SO2)2 - , C(CF2SO2)3 - or a combination thereof, dissolved or dissociated in an organic solvent such as, but not limited to, propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), γ-butyrolactone, or a mixture thereof.
[0079] The electrolyte may be injected at an appropriate stage in the battery manufacturing process depending on the manufacturing process and desired physical properties of the final product, i.e., before battery assembly or at the final stage of battery assembly.
[0080] The present invention also provides a battery module including a battery having an electrode assembly as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source. Specific examples of the device include, but are not limited to, a power tool driven by an electric motor, electric vehicles including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), and the like, electric two-wheeled vehicles including electric bicycles (E-bikes) and electric scooters (E-scooters), electric golf carts, and power storage systems.
[0081] The present invention will be described in detail below with reference to specific examples. However, the examples according to the present invention can be modified into many other forms, and the scope of the present invention should not be construed as being limited to the following examples. The examples of the present invention are provided to more completely explain the present invention to those skilled in the art.
[0082] [Example] The separation membranes of the respective Examples and Comparative Examples were produced by the following method.
[0083] <Example 1> Polyetherimide (PEI, weight average molecular weight: 128,000) and PVDF-HFP (containing 4.4% by weight of repeating units derived from HFP, weight average molecular weight: 744,000) were dissolved in N-methyl-2-pyrrolidone (NMP) as an organic solvent, and Al2O3 nanoparticles with an average particle size of 20 nm were dispersed as inorganic filler to prepare a slurry. The weight ratio of PEI:PVDF-HFP was 6:4, and the weight ratio of PEI+PVDF-HFP:inorganic particles was 4:6. At this time, the solid content in the slurry was 12%.
[0084] The prepared slurry was applied to both sides of a polyethylene porous support (thickness 6.5μm, porosity 37%), and then placed in a coagulation tank filled with water for the NIPS process and dried. The porosity of the inorganic composite porous layer after drying was 81.4%.
[0085] <Examples 2 to 4, Comparative Examples 1 and 2> As shown in Table 1 below, a separation membrane was produced in the same manner as in Example 1, except that the composition of the slurry was changed.
[0086] <Evaluation of separation membrane properties> The physical properties of the separation membranes prepared in the Examples and Comparative Examples were evaluated by the following methods, and the results are shown in Table 1 below.
[0087] [Table 1]
[0088] (1) Measurement of meltdown temperature A 10 mm long separator was placed in a Thermomechanical Analysis (TMA) device (TA Instruments, Q400) and exposed to a temperature rise (5°C / min from 30°C) with a tension of 19.6 mN applied. As the temperature increased, the length of the sample changed, and the temperature at which the length increased rapidly and the sample broke was measured. The meltdown temperature was defined as the meltdown temperature in both the machine direction (MD) and transverse direction (TD).
[0089] (2) Measurement of porosity of inorganic composite porous layer The porosity of the inorganic composite porous layer was measured using the separators prepared in the Examples and Comparative Examples.
[0090] The porosity was measured by measuring the width / length / thickness of the separator to determine the volume, measuring the weight, and calculating the ratio to the weight when the separator occupied 100% of the volume.
[0091] Porosity (%) = {(actual volume) / (compact volume)} / (actual volume) x 100 Compact volume = loading amount / density Actual volume = thickness of the separation membrane
[0092] (3) Evaluation of heat shrinkage rate A separation membrane cut to a size of 5 cm x 5 cm was left in a convection oven at 150°C for 30 minutes, and the change in length in both the machine direction and the transverse direction was measured.
[0093] Heat shrinkage rate (%) = {(dimension before shrinkage - dimension after shrinkage) / dimension before shrinkage} x 100
[0094] (4) Evaluation of adhesive strength The active material [natural graphite and artificial graphite (weight ratio 5:5)], conductive material [Super P], and binder [polyvinylidene fluoride (PVDF)] were mixed in a weight ratio of 92:2:6, dispersed in water, and then coated onto copper foil to prepare the negative electrode, which was then cut to a size of 25 mm x 70 mm.
[0095] The separators prepared in the examples and comparative examples were cut to a size of 25 mm x 70 mm. The separators and negative electrodes were stacked and then sandwiched between 100 μm PET films and bonded using a flat press. The flat press was heated at 60° C. and 6.5 MPa for 1 second.
[0096] The ends of the bonded separator and negative electrode were attached to a Universal Testing System (UTM, manufactured by Instron), and a force was applied at 180° at a measurement speed of 300 mm / min to measure the force required to separate the negative electrode from the separator bonded to the negative electrode.
Claims
1. A separator for an electrochemical element, comprising: The separation membrane comprises a polymeric porous support and an inorganic composite porous layer formed on at least one surface of the porous support, The inorganic composite porous layer contains a binder polymer and an inorganic filler, the binder polymer includes a first binder polymer and a second binder polymer, the ratio of the weight of the first binder polymer to the weight of the second binder polymer is 6:4 to 9:1; the first binder polymer is a non-crystalline polymer having a glass transition temperature (Tg) of 180° C. or more; the second binder polymer is a polyvinylidene fluoride copolymer including a first repeating unit derived from vinylidene fluoride (VDF) and a second repeating unit derived from hexafluoropropylene (HFP); A separator for an electrochemical device, wherein the content of the second repeating unit is 4 to 40 wt % based on the total weight of the polyvinylidene fluoride copolymer.
2. 2. The separator for an electrochemical device according to claim 1, wherein a weight ratio of the first binder polymer to the second binder polymer is from 6:4 to 7:
3.
3. 2. The separator for an electrochemical device according to claim 1, wherein the content of the second repeating unit is 4 to 15 wt % based on the total weight of the polyvinylidene fluoride copolymer.
4. 2. The separator for an electrochemical device according to claim 1, wherein the inorganic composite porous layer has a porosity of 70% or more.
5. 2. The separator for an electrochemical device according to claim 1, wherein the first binder polymer comprises polyimide (PI), polyamideimide (PAI), polyetherimide (PEI), polyphenylsulfone (PPSU), polyethersulfone (PES), polysulfone (PSU), or two or more thereof.
6. 2. The separator for electrochemical devices according to claim 1, wherein the inorganic filler is a primary particle having an average particle size of 20 nm to 700 nm.
7. The inorganic filler is alumina (Al 2 O 3 ), fumed alumina, aluminum hydroxide (Al(OH) 3 ), magnesium hydroxide (Mg(OH) 2 2. The separator for an electrochemical device according to claim 1, comprising: SiO2 (AlOOH); boehmite (AlOOH); or two or more of these.
8. 2. The separator for an electrochemical device according to claim 1, wherein the inorganic composite porous layer further comprises 3 parts by weight or less of a dispersant based on 100 parts by weight of the inorganic composite porous layer.
9. 9. The separator for an electrochemical device according to claim 8, wherein the dispersant is polyvinylpyrrolidone (PVP).
10. An electrochemical device comprising a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, An electrochemical element, wherein the separator is the separator for electrochemical elements according to claim 1 .
11. The electrochemical device according to claim 10, wherein the electrochemical device is a lithium secondary battery.
12. A method for producing the separator for electrochemical elements according to claim 1, (S1) preparing a polymeric porous support; (S2) applying a slurry containing a binder polymer, an inorganic filler, and a solvent to at least one surface of the polymeric porous support; (S3) immersing the polymeric porous support coated with the slurry in a composition containing a non-solvent and drying the composition to form an inorganic composite porous layer; the binder polymer includes a first binder polymer and a second binder polymer, the ratio of the weight of the first binder polymer to the weight of the second binder polymer is 6:4 to 9:1; the first binder polymer is a non-crystalline polymer having a glass transition temperature (Tg) of 180° C. or more; the second binder polymer is a polyvinylidene fluoride copolymer including a first repeating unit derived from vinylidene fluoride (VDF) and a second repeating unit derived from hexafluoropropylene (HFP); A method for manufacturing a separator for an electrochemical device, wherein the content of the second repeating unit is 4 to 40 wt % based on the total weight of the polyvinylidene fluoride copolymer.
13. The method for producing a separator for an electrochemical element according to claim 12, wherein the solvent is an organic solvent.
14. 13. The method for producing a separator for an electrochemical element according to claim 12, wherein the non-solvent comprises water, methanol, ethanol, propyl alcohol, butyl alcohol, butanediol, ethylene glycol, propylene glycol, tripropylene glycol, acetone, tetrahydrofuran, methylene chloride, chloroform, dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone, cyclohexane, isopropyl alcohol, or two or more of these.
Citation Information
Patent Citations
Coating slurry material for separators and preparation method of material, lithium ion battery separator and preparation method thereof, and lithium ion battery
CN109301134A
Reticle pod
JP2012177930A
Separator for nonaqueous secondary battery, nonaqueous secondary battery, method for manufacturing separator for nonaqueous secondary battery, and coating composition for nonaqueous secondary battery
JP2019029314A
Integrated Process for Producing BTX and Hydrogen from Shale Gas with Feeding of Carbon Dioxide
KR1020230064182A
Wire pipe manufacturing apparatus having a wire support structure
KR102090544B1